Pol??tica monet??ria e dep??sitos compuls??rios em uma pequena economia aberta - Haraguchi, Carlos Alberto Takashi (2016)
This work evaluates the effects of shocks on a small open economy using a DSGE model with financial frictions and a macroprudential measure of reserve requirements with monetary authority. According to this approach, the exchange rate role as a channel of transmission for shocks was analyzed as well as alternatives Taylor rules and reserve requirements policies the monetary authority could implement. Simulations indicated exchange rate plays an active role in situations of domestic or external monetary policy and technological progress shocks, but the intensity depends on the degree of openness of the economy. The choice between PPI or CPI measures of inflation as a target in the Taylor rule resulted in a slight better performance for PPI regarding stability. When it comes to including real exchange rate in the rule, the differences were more significant, indicating that, in order to reach a common inflation target, the necessary interest rate shock and the ensuing fall of output would be smaller as well as the convergence to equilibrium would be faster. However, the cost was a more volatile inflation rate. The absence of reserve requirements with monetary authority was more appropriate in case of external shocks, since it caused lower volatility in output and domestic prices. A reserve requirements policy, on the other side, helped to stabilize output after a internal monetary policy shock.